Exploring problems and needs in disaster preparedness : a qualitative study - Harianto, Joanggi Wiriatarina; Nuntaboot, Khanitta (Jurnal Ners, 2023)
Introduction: Disasters are sudden, unplanned events that cause damage and loss to people. The way people understand or interpret disasters that occur is very diverse, so they respond and act on differently in anticipating future disasters that may occur in their environment. There is also diversity in problems and needs based on community perception. The purpose of this research is to explore the problems and needs related to disaster preparedness in the community. Methods: An ethnographic study was conducted from September 2021 until July 2022 at Central Sulawesi. Twentyfive participants who met the inclusion criteria were involved through purposive sampling. The inclusion criterion was communities who directly affected by the Palu disaster on September 28, 2018. Researchers used a semi-structured interview guide as a data collection tool. Recording devices were used during the interviews. Interview data were recorded verbatim and the data analysis process was based on Gerrish and Lacey. Checking members and bold descriptions was done to maintain the validity of the data. Results: Three main themes were found from emerging data, 1) Health support needs, 2) Knowledge support needs, and 3) Disaster support system needs., the researchers asked both community members and parties concerning problems and needs in regard to preparedness related to disasters. Conclusions: Information support related to disasters, technology support especially in terms of early warning systems, as well as socialization and first aid training for health are needed for the community to support the sustainability of disaster preparedness in the community.